Nano-adsorbents for the removal of metallic pollutants from water and wastewater - Sharma Y.C.; Srivastava V.; Singh V.K.; Kaul S.N.; Weng C.H. (My University, 2025)
Of the variety of adsorbents available for the removal of heavy and toxic metals, activated carbon has been the most popular. A number of minerals, clays and waste materials have been regularly used for the removal of metallic pollutants from water and industrial effluents. Recently there has been emphasis on the application of nanoparticles and nanostructured materials as efficient and viable alternatives to activated carbon. Carbon nanotubes also have been proved effective alternatives for the removal of metallic pollutants from aqueous solutions. Because of their importance from an environmental viewpoint, special emphasis has been given to the removal of the metals Cr, Cd, Hg, Zn, As, and Cu. Separation of the used nanoparticles from aqueous solutions and the health aspects of the separated nanoparticles have also been discussed. A significant number of the latest articles have been critically scanned for the present review to give a vivid picture of these exotic materials for water remediation. © 2009 Taylor & Francis.